DAYA TARIK WISATA SAMPAN JONG PANTAI INDAH SELAT BARU KABUPATEN BENGKALIS PROVINSI - Try Sarah; Siti Sofro Sidiq (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
People’s games like Jong is a tourism potential that has the opportunity to serve as a tourist attraction. This Jong game is not his tough play.but to make the Jong it self is still very difficult. This is the cause of Jong boat is unique and rare also seem luxurious.Jong canoe is also a coastal folk game that still survives to this dayThis study aims to find out how to draw the charm of Jong and know the responses of tourists about the tourist attraction of Jong boat in the beautiful beaches selatbaru regency bengkalis. This research uses quantitative descriptive method to examine the issues raised by analyzing the responses of tourist who come to see the tourist attraction Jong boat. As for the questionnaires distributed as many as 30 people. While collection techniques in this study using observation, interviews, questionnaires, and documentation.The result of this study indicate that the response of tourists to the tourist attraction on the tourist attraction beautiful coastal boat Jong selatbaru Bengkalis district of Riau province is quite agree with the overall score is the amount 780-1019. Jong boat tourist attraction is done aims to entertains bengkalis district community.Jong is one of the attractions in the beautiful beach of new bengkalis strait that can bring increased tourist. The refore the game that is expected is not every year, but on the birthday of the cityKeywords : Tourist Attractions,Canoe Jong, Folk Games Bengkalis Regency